Analisis Yuridis Terjadinya Peristiwa Konflik Bersenjata Ukraina dan Rusia Ditinjau dari Perspektif Hukum Humaniter Internasional - Asya, Jasran; Rahayu, Sakthi; Widianto, Alfin Prananda (LPPM Universitas Ekasakti Padang, 2024)
Over the past half century, almost every country has been involved in armed conflicts either domestically or with other nations. One example is the escalating armed conflict between Ukraine and Russia, resulting in many civilian casualties and damaging public infrastructure, which is considered a violation of the provisions of international humanitarian law. This research was conducted using normative juridical methods by examining legal materials obtained through literature study. The findings of this research indicate that the Russian Armed Forces have committed various violations contrary to the principles of humanitarian law, such as the principles of military necessity, humanity, and proportionality. Violations of these principles may include disproportionate attacks, targeting civilians, excessive use of force, and restrictions on humanitarian assistance. Resolving this conflict requires a comprehensive approach and the commitment of all parties involved, such as urging Russia and Ukraine to fulfill their obligations as UN members by respecting applicable international humanitarian law provisions under the principle of pacta sunt servanda, mediating through diplomatic channels, imposing sanctions by the UN against both countries for violations of international humanitarian law as accountability for the attacks committed, and urging the UN Security Council to issue a resolution to immediately cease the hostilities.